Social legitimacy of private tutoring: an investigation of institutional and affective educational practices in India. Issue 4 (4th July 2022) - Gupta, Achala
ABSTRACT: While a growing body of research shows the prevalence of private tutoring in India, the ways in which these informal educational setups gain social legitimacy remains largely unclear. To redress this gap in the scholarship, this article investigates institutional and affective tutoring practices, in relation to formal schooling. It draws on the perspectives of tutors, school teachers, teacher-tutors, students and their parents, produced through an educational ethnography conducted in Dehradun (India) in 2014–2015. In so doing, this article shows that strategic adoption (adhering to formal education practices) and tactical deviation (diverging from typical schooling norms) are central to tutoring centres' attempt to project themselves as academically relevant and desirable spaces for teaching and learning. By offering a nuanced understanding of the interactions between formal (schools) and informal (tutoring provisions) educational institutions, it argues that private tutoring serves as a critique of formal schooling in the empirical context.